POTENSI KEBAKARAN HUTAN PADA GUNUNG SUMBING SETIAP MUSIM PANAS - Purba, Christina Aprilieni; Artanti, Irma; Rahayu, Rina (Journal of Forestry And Environment, 2024)
Forests are natural ecosystems that consist of large areas of land that contain many biological resources. Forest fires have several factors, namely due to human activity, high air temperatures. In this study, the cause of forest fires on Mount Sumbing is due to very hot air temperatures, the temperature this year is hotter than the average, this is due to the phenomenon of hot air trapped in the area due to anomalous atmospheric dynamics. The purpose of this study is to determine the potential for summer to cause forest fires on Sumbing Mountain. The research method used is qualitative descriptive analysis based on the results of drought index management related to the distribution of hot spots in 2023. The results of the research studied by the researcher are the fires that occurred in the Mount Sumbing forest on Friday, 1 which resulted from hot weather. So the potential for forest fires that occur on Mount Sumbing during hot weather has a very large potential and causes serious forest fires, therefore the guards on Mount Sumbing are dexterous if unwanted things happen such as evacuating residents and climbers